DOES THE USE OF AN ADHESIVE IMPROVE CONVENTIONAL COMPLETE DENTURES? -literature review - Dana Gabriela Budală; Zinovia Surlari; Raluca Baciu; Maria Bolat; Florinel Cosmin Bida; Dragoș Ioan Virvescu; Roxana Ionela Vasluianu (Romanian Society of Oral Rehabilitation, 2022)
Denture adhesives, when used properly are safer and beneficial to the patient in improving retention and stability, incisive ability, comfort, function, and in providing psychological security. Although adhesives enhance denture performance and patient confidence, they should not be used to compensate denture deficiencies. The patients should use denture adhesives only on the advice of their dentists and the dentists too should instruct them about the proper use and caution against misuse of denture adhesives.